ADHD subjects fail to suppress eye blinks and microsaccades while anticipating visual stimuli but recover with medication - Fried, Moshe; Tsitsiashvili, Eteri; Bonneh, Yoram S.; Sterkin, Anna; Wygnanski-Jaffe, Tamara; Epstein, Tamir; Polat, Uri (Vision research (Oxford), 2014)
•Blink and saccade rates were higher in ADHD subjects in a continuous performance task.•Medication reduced the saccade rate to control levels, and lowered the blink rate.•ADHD subjects fail to suppress saccades and blinks while anticipating stimuli. Oculomotor behavior and parameters are known to be affected by the allocation of attention and could potentially be used to investigate attention disorders. We explored the oculomotor markers of Attention-deficit/hyperactivity disorder (ADHD) that are involuntary and quantitative and that could be used to reveal the core-affected mechanisms, as well as be used for differential diagnosis. We recorded eye movements in a group of 22 ADHD-diagnosed patients with and without medication (methylphenidate) and in 22 control observers while performing the test of variables of attention (t.o.v.a.). We found that the average microsaccade and blink rates were higher in the ADHD group, especially in the time interval around stimulus onset. These rates increased monotonically over session time for both groups, but with significantly faster increments in the unmedicated ADHD group. With medication, the level and time course of the microsaccade rate were fully normalized to the control level, regardless of the time interval within trials. In contrast, the pupil diameter decreased over time within sessions and significantly increased above the control level with medication. We interpreted the suppression of microsaccades and eye blinks around the stimulus onset as reflecting a temporal anticipation mechanism for the transient allocation of attention, and their overall rates as inversely reflecting the level of arousal. We suggest that ADHD subjects fail to maintain sufficient levels of arousal during a simple and prolonged task, which limits their ability to dynamically allocate attention while anticipating visual stimuli. This impairment normalizes with medication and its oculomotor quantification could potentially be used for differential diagnosis.